Pengalaman Dzikir dan Kontemplasi dalam Bimbingan Spiritual Tarekat Tijaniyah di Madura, Indonesia - Moh. Wardi; Mudiuddin; Heri Fadli Wahyudi (KURAS Institute, 2024)
The balance between human physical and psychological aspects is essential. In today's technological age, many individuals tend to prioritize material possessions, often at the expense of their inner needs. To address this imbalance, it is vital to incorporate spiritual dimensions, especially those that focus on the relationship with God. Sufism, particularly through practices such as the Tarekat Tijaniyah, offers spiritual guidance that enables individuals to attain peace of mind.This study explores the role of spiritual guidance through dhikr within the tarekat as a means of enhancing the spiritual quality of its followers. A qualitative approach, utilizing phenomenological research, is employed to understand the experiences of adherents of Tarekat Tijaniyah in the Pragaan Subdistrict. The findings indicate that through the regular and heartfelt practice of wirid and dhikr, followers experience profound spiritual moments that cultivate admirable qualities such as sincerity, patience, tawakkal (trust in God), and gratitude. This underscores the importance of achieving a balance between the spiritual and material aspects of life, resulting in inner peace and reinforced faith. The spiritual guidance provided by the muqoddam includes enlightenment, counsel, and practical spiritual exercises. The personality and charisma of the muqoddam serve as significant role models, promoting religious discipline and enriching the spiritual and mental lives of the community, ultimately benefiting society as a whole.